2003
DOI: 10.1093/bja/aeg130
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular regional wall motion abnormalities during pneumoperitoneum in children

Abstract: Pneumoperitoneum may affect LV regional wall motion in paediatric patients undergoing laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The use of minimal pressure nevertheless is advocated because tolerance is unknown above 13 mm Hg, and the stability of the arterial pressure does not exclude alterations of the cardiac output. 24,25 Postoperative hypothermia was frequent and the final temperature was Ͻ35°C in 25% of the infants. The heightened sensitivity to hypothermia in the newborns, caused by an increased caloric loss and a per-operative drop in thermogenesis, was aggravated by the frequently prolonged surgical times and the use of cold and dry gas.…”
Section: Discussionmentioning
confidence: 99%
“…The use of minimal pressure nevertheless is advocated because tolerance is unknown above 13 mm Hg, and the stability of the arterial pressure does not exclude alterations of the cardiac output. 24,25 Postoperative hypothermia was frequent and the final temperature was Ͻ35°C in 25% of the infants. The heightened sensitivity to hypothermia in the newborns, caused by an increased caloric loss and a per-operative drop in thermogenesis, was aggravated by the frequently prolonged surgical times and the use of cold and dry gas.…”
Section: Discussionmentioning
confidence: 99%
“…Huettemann et al found significant septal hypokinesia at an IAP of 12 mmHg in paediatric patients undergoing laparoscopic surgery. 6 In our patient the IAP was kept below 10 mmHg and all the time we did not observe any episode of hypotension or bradycardia throughout the conduct of anaesthesia.…”
Section: Discussionmentioning
confidence: 48%
“…TULAA and CMLA both require pneumoperitoneum to provide a superior view, but this can sometimes cause a decrease in venous return and hypokinesia of the heart, particularly in children [35][36][37]. TULAA also requires more specialized devices than CMLA, including a peculiar trocar [13,26] and an automatic sewing/ligation device [14][15][16].…”
Section: Discussionmentioning
confidence: 99%